Analisis Penerapan Strategi Promosi Menggunakan Media Sosial untuk Meningkatkan Minat Beli Konsumen pada Produk Olahan Rinuak di Jorong Bancah (Studi Kasus: UMKM Tapian Maninjau) - Muhamad Choirul Yahya; Santi Deswita (ARZUSIN, 2026)
Although promotional strategies through social media have been widely studied in digital marketing, research specifically analyzing their implementation in local product-based micro, small, and medium enterprises (MSMEs) to increase consumer purchase intention remains limited. This study aims to analyze the implementation of promotional strategies through social media in increasing consumer purchase intention at Tapian Maninjau MSME. This study employed a qualitative approach with a case study design. The research informants consisted of the MSME owner, consumers, and supporting informants selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results showed that Facebook and WhatsApp had been utilized as promotional and communication channels with consumers, thereby facilitating the dissemination of product information and expanding marketing reach. However, the implementation of these strategies was not yet optimal because promotional activities remained limited to simple posts, were not supported by content planning and promotional evaluation, and had not maximized the use of various digital platforms. In addition to social media promotion, product quality, taste, packaging, and customer recommendations also influenced consumer purchase intention. These findings strengthen the application of the concepts of the marketing mix, social media marketing, and purchase intention in the context of local product-based MSMEs. This study emphasizes that optimizing social media promotion requires improved digital literacy, content planning, periodic evaluation, and platform diversification to strengthen consumer purchase intention and MSME competitiveness in the digital era.